Growth and Brix of Sweet Sorghum under Different Fertilizer Application in Maginal Land - Rukmowati Brotodjojo; Mohammad Nurcholis; T Marnoto; Ari Wijayani; Rochman Isdiyanto (Jurnal Agrivet, 2017)
Sorghum is one of the commodities that are potentially very good to meet the needs of food, feed, industrial and renewable energy sources. Sorghum has protein, iron and calcium content that is much higher than rice. Additionally, sorghum has wide adaptability and is a plant that is tolerant to drought and low fertility. Therefore it can be cultivated on marginal lands. This study aimed to study the effects of fertilization on the growth and brix value of sweet sorghum cultivated on marginal land. The experiment was arranged in randomized completely block design, with three treatments, namely NPK, NPK + LOF (Liquid Organic Fertilizer) / 1 week, NPK + LOF/ 2 weeks. Each treatment consisted of 5 replication, and for each replication 6 plant samples was observed. Each plot consisted of 12 rows and in each row there were 7 plants. Sorghum was planted with the distance between rows 75 cm and the distance between plants in rows was 30 cm. The data was subjected to analysis of variance followed by Duncan’s Multiple Range Test. The application of NPK fertilizer plus LOF once a week resulted in significantly higher plant height, number of leaves and brix value compared to NPK fertilizer plus LOF fortnightly or just NPK fertilizer alone. Fertilization treatment did not significantly affect sorghum stem diameter, except at the age of 3 weeks after planting.Keywords: fertilization, growth, brix, sweet sorghum.